An Unusual Presentation of Tumor Lysis Syndrome in a Patient with Advanced Gastric Adenocarcinoma: Case Report and Literature Review. (27th May 2012) - Vodopivec, Danica Maria; Rubio, Jose Enrique; Fornoni, Alessia; Lenz, Oliver
Abstract : Tumor lysis syndrome (TLS) is characterized by hyperuricemia, hyperkalemia, hyperphosphatemia, and secondary hypocalcemia in patients with a malignancy. When these laboratory abnormalities develop rapidly, clinical complications such as cardiac arrhythmias, acute renal failure, seizures, or death may occur. TLS is caused by rapid release of intracellular contents by dying tumor cells, a condition that is expected to be common in hematologic malignancies. However, TLS rarely occurs with solid tumors, and here we present the second chemotherapy-induced TLS in a patient with advanced gastric adenocarcinoma to be reported in the literature. We also provide information regarding the total cases of TLS in solid tumors reported from 1977 to present day. Our methodology involved identifying key articles from existing reviews of the literature and then using search terms from these citations in MEDLINE to find additional publications. We relied on a literature review published in 2003 by Baeksgaard et al., where they gathered all total 45 cases reported from 1977 to 2003. Then, we looked for new reported cases from 2004 to present day. All reports (case reports, brief reports, letters to editor, correspondence, reviews, journals, and short communications) identified through these searches were reviewed and included.